Discourse communication in Japanese Language among Malaysian tourist guides: Communication criteria and strategy - Mamat, Roslina; Abd Rahim, Normaliza (The International Journal of Learning, 2008)
This study looks at Japanese communication of the Malaysian tourist guides while communicating with Japanese tourists. 50 questionnaires have been distributed randomly to the tourist guides to determine the majority of their background. The conversation between the tourist guides and the Japanese tourists were taped via a tape recorder and the duration of the communication was 4 hours. The data were analyzed based on the communication criteria and strategy used. This method was used by the writer to determine the weaknesses in the communication and at the same time open up a space to others; other tourist guides, travel agency and the staff at the tourism center to improve their weaknesses for the sake of everyone. In conjunction with the “Visit Malaysia Year 2007”, it is hoped that this study can open up everyone’s mind and eyes, especially those who are involved in the tourism sector to be aware with the weaknesses of these tourist guides in this industry. To attract more Japanese tourists to Malaysia, the government agency should not shut their eyes to the difficulties the travel/tourism agency and tourism center have in getting more professional tourist guides. Trainings and courses are necessary to be given to the existing tourist guides and at the same time able to produce more capable tourist guides. At this moment, this study is to show our weaknesses as a host. And as a host, it is clear that these weaknesses need to be dealt with immediately if we want the plan to attract 500,000 Japanese tourists to succeed.